A bimetallic Ag15Cu12(S-c-C6H11)18(CH3COO)3 nanocluster featuring an irregular Ag12 kernel. Issue 4 (4th January 2023) - Lin, Zhenzhen; Zhang, Ting; Fang, Cao; Jin, Shan; Xu, Chang; Hu, Daqiao; Zhu, Manzhou
Abstract : A novel Ag–Cu bimetallic nanocluster Ag15 Cu12 (S- c -C6 H11 )18 (CH3 COO)3 consisting of an irregular Ag12 core and a stabilizing Ag3 Cu12 (SR)18 (CH3 COO)3 shell was synthesized. The optical properties were characterized experimentally and theoretically. Abstract : Here, we report the synthesis and atomic structure of a Ag15 Cu12 (SR)18 (CH3 COO)3 ·(C6 H14 ) nanocluster (Ag15 Cu12 for short, SR denotes cyclohexanethiol), confirmed by single-crystal X-ray diffraction (SC-XRD), electrospray ionization mass spectrometry (ESI-MS), X-ray photoelectron spectroscopy (XPS) and thermogravimetric analysis (TGA). X-ray crystallographic analysis revealed that Ag15 Cu12 consisted of an irregular Ag12 core, stabilized by the Ag3 Cu12 (SR)18 (CH3 COO)3 shell. The shell consisted of two nearly planar Cu3 (SR)6 moieties, three monomeric [–SR–Ag–SR–] units and three Cu2 (CH3 COO) staples. Furthermore, time-dependent density functional theory (TD-DFT) simulation was performed to interpret the optical absorption features of Ag15 Cu12 . Overall, this work will broaden and deepen the understanding of Ag–Cu alloy nanoclusters.